Procedure for Issuing Revolying Loans Revolving Loans in Rural Areas, Seruyan Hilir Regency - Sari Hayati (Riwayat: Educational Journal of History and Humanities, 2023)
The purpose of this study was to determine how the lending procedures scrolling national program for community empowerment rural to small and medium enterprises rural communities in Sub Seruyan Hilir, to determine the obstacles that arise facing society and unit financial management in the process of granting credits rolled national community empowerment program mandiri rural small and  medium enterprises to rural communities in Sub Seruyan Hilir. This research is a qualitative descriptive study. Based on the source, there  are two primary data and secondary data, data collection techniques used were interviews, observation, and documentation. Based on the results of this study concluded that, revolving credit granting procedures of the national program of rural community empowerment through 6 stages, stages of the loan application, the examination of the loan, the loan decision phase, the realization phase, development phase of the loan, the loan repayment phase. Constraints arising in the provision of revolving credit, namely, the slow process of obtaining loans by the Financial Management Unit, there are arrears in installments, or bad loans of the group of governmental and often misuse the name of the borrower members  group of governmental . Solutions to problems that arise, provide faster service to the community, conduct home visits to members of self help groups that are in arrears and financial management unit more careful in conducting the examination stage loans.